Synthesis of Epilepsy Drug Brivaracetam through Solvent-free Lactamization - Singh, Saurabh Kumar; Ghosh, Partha; Prasad, Rajendra (Letters in Organic Chemistry, 2025)
Brivaracetam is a relatively new racetam drug for the treatment of epilepsy, synthesis of which with proper stereocontrol remains challenging. Herein we describe a solvent-free lactamization method for the development of two efficient synthetic routes to brivaracetam. The key method is a one-step condensation of amines with chiral α-carboxyethyl-β-propyl butyrolactone under neat conditions that proceed through tandem decarboxylation and lactamization. The lactam obtained using benzylamine was converted to (S)-3-propyl pyrrolidinone, a key intermediate to brivaracetam. Whereas, the lactam obtained from the condensation of (S)-2-amino butanol was further transformed into brivaracetam.
Keywords: tandem reaction